Prevalência de cárie dentária em escolares de 7 a 12 anos de idade, na cidade de Araraquara, SP (Brasil), 1979 - Vasconcellos, Maria do Carmo Costa [UNESP] (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 1982)
São apresentados os resultados de levantamento epidemiológico de cárie dentária em escolares de 7 a 12 anos de idade da cidade de Araraquara, SP, Brasil, cuja água de abastecimento público é fluoretada. O objetivo do estudo é verificar a prevalência de caria dentária e o nível de assistência odontológica oferecido a esta população. A população de estudo compõe-se de escolares nascidos e sempre residentes na cidade e escolares não nascidos e/ou nem sempre residentes na cidade; são comparados os índices CPO-D obtidos para os dois grupos.

The results of a survey of the prevalence of dental caries in 7-12 year-old school children of Araraquara, S. Paulo, Brazil users of fluoridated water are presented. The purpose of the survey was to discover both the prevalence of dental caries and the amount of dental treatment offered to the school population. The data have been organized to show the DMF index difference between children born and reared in the city and those neither born nor continuously resident in the city. As no significant statistical difference was observed between these groups (except among the 12 year olds) the fluoride concentration in public water was examined and its absence was detected.
Prevalence of dental caries in 7-12 year-old school children of Araraquara, S. Paulo, Brazil, in 1979
Keywords: Inquérito epidemiológico; Cárie dentária; Araraquara, SP, Brasil; Escolares; Índice CPO-D; Dental caries; Araraquara, SP, Brazil; School Children; DMF index